Mukjizat Dan Sihir: Analisis Pragmatik Dalam Kisah Para Rasul Serta Relevansinya Pada Konteks Kontemporer - Talifuddin, Fiona Isaura; Lintong, Aurel Chirstania Alexandra (Vieka Wahana Semesta, 2025)
Miracles and magic are two things whose meanings are often related in people's lives. Both lead to a miraculous act that sometimes people find it difficult to distinguish which miracles are from miracles and which are from magic. This study analyzes the two words in the context of the Acts of the Apostles and their relevance in the contemporary context. The research method used is qualitative research with a pragmatic linguistic approach to understand the meaning that arises from the context at that time. The results showed that the use of the word